Framework Assessment of Sustainable Roads Infrastructure In Indonesia - Hidayat, Bagus Radham; Rohman, Mohammad Arif (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2024)
Assessment of the road infrastructure's sustainability is necessary in order to determine its level of sustainability and usefulness. The purpose of this study to develop standards for sustainable road and Variable a framework for assessing road infrastructure's sustainability. Frameworks The road sustainability assessment is derived by choosing sustainable criteria from theoretical research and discussing with road experts. The variables are then reduced using a relative importance index, and the variables are distributed using a paired comparison questionnaire. This process is managed using the Analytical Hierarchy Process (AHP) method. Afterwards, the model for assessing road sustainability was tested on a road object used for this assessment was Fuzzy Comprehensive Evaluation (FCE) method. The evaluation of the Framewok analysis, It covers nine sub-criteria for social sustainability, six sub-criteria for economic sustainability, four sub-criteria for environmental sustainability, and three sub-criteria for management sustainability.